Green accounting, firm size on financial performance in Jakarta Islamic Index / Sri Rahayu … [et al.] - Rahayu, Sri; Effendi, Syamsul; Artika, Valia Salsa; Karina Putri, Adisty Alifia; Habibie, Azwansyah; Listiorini, Listiorini; Suginam, Suginam (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
The purpose of this study was to determine the effect of implementing green accounting, company size on the financial performance of companies listed on the Jakarta Islamic index (JII). In this study green accounting can be measured using the dummy method. And this research is quantitative research, and the data used is in the form of financial reports that have been published by companies on their respective websites. The sample used is a company registered on the Jakarta Islamic index for the 2019-2021 period. The sampling technique was purposive sampling with a total sample of 20 companies. Partially, the results of the study show that green accounting has no effect on financial performance and company size has an effect on the financial performance of companies listed on the Jakarta Islamic Index. Simultaneously, it shows that green accounting and company size have no effect on the financial performance of companies listed on the Jakarta Islamic Index.